THE STUDENTS’ READING COMPREHENSION THROUGH NEUROLOGICAL IMPRESS METHOD (N.I.M) AT THE EIGHT GRADE OF MTS AL-MANSUR BIANGLOE - Ina Syahriani; Bahrun Amin; Muh. Zia Ul Haq (Journal of Language Testing and Assessment, 2022)
This research aimed at improves the students’ reading ability at the eighth grade through Neurological Impress Method in term of literal comprehension dealing with main idea and supporting details.To explain the improvement, the researcher used a classroom action research (C.A.R) which was conduct in two cycles in which every cycle consisted of four meetings. The location of this research was taken at the eighth grade students of MTS Al-Mansur Biangloe with a number of the subject were 20 students.The research findings indicated that the application of Neurological Impress Method was Significant in improving the students reading ability in term of literal comprehension dealing with main idea and supporting details. It was proved by the mean score of cycle I was 40. It was classified as poor then improve to be 83.75. It was classified as good in cycle II. They are higher than the mean score of diagnostic test namely 32.5 that classified as very poor. Therefore, there was the improvement of the students reading ability in teaching and learning process from cycle I to cycle II in term of literal comprehension dealing with main ideas and supporting details.